Burnout - Rakovec-Felser Zlatka; Pernat Drobež Cvetka (Acta Medico-Biotechnica, 2021)
This article is devoted to burnout in medical care. Except a definition of phenomenon as a result of imbalance between work demands and resources, physician’s caring for others and caring for oneself, the complex interactions between the external and the internal causes of professional burnout are highlighted. It informs us also with manifestations, signs, and the phases of a triggered burnout process. As North American and European research data in the comparison with the general population reveal higher extent of burnout among physicians, authors emphasize that higher extent of burnout is not only a physicians’ problem, but because of its epidemic character and consequences a vital element of quality and patient outcomes, well–functioning health care system as well as public health in general. They pointed out that the effective prevention programs and helping interventions needs to go in both directions – interventions of medical organization as well as the preventive interventions on an individual level. The latter are presented in the article upon completion.